2022
DOI: 10.1093/bjd/ljac132
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depression, anxiety and severe mental illness among adults with atopic eczema or psoriasis: a systematic review and meta-analysis

Abstract: Background Evidence suggests an association between atopic eczema (AE) or psoriasis and mental illness. However, factors associated with mental illness are unclear. Objectives To synthesise and evaluate all available evidence on factors associated with depression, anxiety, and severe mental illness (SMI) among adults with AE or psoriasis. Methods We searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
0
11
1
Order By: Relevance
“…Consequently, body weight emerges as a significant cofactor influencing the prevalence of mood disorders among psoriatic patients, in addition to the severity of skin lesions. Interestingly, contrary to our results, a recent meta-analysis proposed a greater predisposition of female sex among psoriatic patients (OR = 1.62, 95% CI 1.09–2.40) [ 45 ]. A nationwide population-based cross-sectional study in Taiwan identified female sex and major comorbid diseases, including cardiovascular disease, as major risk factors associated with depression among psoriatic patients [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, body weight emerges as a significant cofactor influencing the prevalence of mood disorders among psoriatic patients, in addition to the severity of skin lesions. Interestingly, contrary to our results, a recent meta-analysis proposed a greater predisposition of female sex among psoriatic patients (OR = 1.62, 95% CI 1.09–2.40) [ 45 ]. A nationwide population-based cross-sectional study in Taiwan identified female sex and major comorbid diseases, including cardiovascular disease, as major risk factors associated with depression among psoriatic patients [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…CPRD is an ongoing, nationwide database of routinely collected primary care records including information on demographics, diagnoses, symptoms, and prescriptions 31 . Morbidity code lists and all analytic codes used in this study are available for download 32 …”
Section: Methodsmentioning
confidence: 99%
“…We used a directed acyclic graph (DAG) and a systematic review to inform covariate selection (Appendix S2 ). 38 , 39 We matched age, sex, and practice (as an indirect means of accounting for differences in coding practice, rural/urban location, and socioeconomic deprivation). We considered age, sex, calendar period (2006–2010, 2011–2015, 2016–2020) and deprivation (quintiles of individual‐level Carstairs Index used when available, and practice‐level Carstairs if not) as potential confounders.…”
Section: Methodsmentioning
confidence: 99%
“…We used directed acyclic graphs (DAGs) and a systematic review to inform covariate selection ( Appendix S2 ). 31 , 32 We matched on age, sex, and general practice, and considered calendar time (1997–2003, 2004–2009, 2010–2015, 2016–2020) and deprivation (quintiles of patient-level Carstairs Index used when available, otherwise practice-level Carstairs Index used) as potential confounders. 33 We considered the following variables as potential mediators: comorbidity burden (using the Charlson Comorbidity Index), 34 body mass index (BMI), smoking status, harmful alcohol use, and in AE only, sleep problems and high-dose glucocorticoid use.…”
Section: Methodsmentioning
confidence: 99%